Transfer learning technique applied to multispectral images classification problem - Yaloveha, V.; Podorozhniak, A. (Національний технічний університет "Харківський політехнічний інститут", 2023)
The purpose of the report is to research multiple pretrained convolutional neural network families to serve as baseline models for the remote sensing dataset benchmarking.
Keywords: Convolutional neural networks; VGG-16; convolutional neurons; deep neural networks; neural network architecture